2019
DOI: 10.5194/acp-2019-751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between the molecular composition, visible light absorption, and health-related properties of smoldering woodsmoke aerosols

Abstract: <p><strong>Abstract.</strong> Organic aerosols generated from the smoldering combustion of wood critically impact air quality and health for billions of people worldwide; yet, the links between the chemical components and the optical or biological effects of woodsmoke aerosols (WSA) are still poorly understood. In this work, an untargeted analysis of the molecular composition of smoldering WSA, generated in a controlled environment from nine types of heartwood fuels (A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…As a result, outdoor and indoor exposure to biomass burning smoke is an important and growing health risk factor. As previously suggested, the responses induced by the organic fraction of biomass burning smoke are not linked solely to PAH content; rather, they are also associated with other organic compounds [25,56]. High-resolution aerosol mass spectrometry (HR-AMS), TEM, and Fourier transform infrared spectroscopy (FTIR) results have suggested that wood tar aerosols may serve as proxies for biomass burning aerosols [19].…”
Section: Discussionmentioning
confidence: 96%
“…As a result, outdoor and indoor exposure to biomass burning smoke is an important and growing health risk factor. As previously suggested, the responses induced by the organic fraction of biomass burning smoke are not linked solely to PAH content; rather, they are also associated with other organic compounds [25,56]. High-resolution aerosol mass spectrometry (HR-AMS), TEM, and Fourier transform infrared spectroscopy (FTIR) results have suggested that wood tar aerosols may serve as proxies for biomass burning aerosols [19].…”
Section: Discussionmentioning
confidence: 96%
“…The nitrate anion, prominently detected in the mass analyzer at m/z 61.988, was not purposefully introduced but likely formed either from in-source fragmentation of organic ni-trates or from HNO 3 produced during the hydrolysis of tertiary organonitrates from the aqueous LC solvents and fortuitously acted as a reagent ion for chemical-assisted electrospray. While peak heights correlate well with concentration in direct-infusion ESI HRMS when the analyte matrix is similar (Chan et al, 2020), the correlation coefficients are unknown for each analyte in the mixture; thus, the HRMS data are qualitative. Furthermore, due to the labile -ONO 2 groups, the organonitrate observations from HRMS likely represent a lower limit.…”
Section: Soa Composition Analysis By High-resolution Mass Spectrometry (Hrms)mentioning
confidence: 99%
“…Air pollution characterized by fine particulate matter (PM 2.5 , with aerodynamic diameter less than 2.5 μm) has attracted considerable attention due to its significant impact on global air quality 1 , climate change 2,3 , and human health [4][5][6] . Secondary aerosol formation is the main driver of PM 2.5 pollution 7,8 .…”
Section: Introductionmentioning
confidence: 99%